PARTAI POLITIK dan SISTIM DEMOKRASI DI INDONESIA - Ayub Muksin (Populis : Jurnal Sosial dan Humaniora, 2018)
The Republic of Indonesia since 1945 when it proclaimed its independent from the Dutch colonialism adopted democracy as political system. In its political development, democracy in Indonesia had many names or label. From 1945 until 1959, the Republic of Indonesia adopted and implemented which   is commonly known as Liberal Democracy. During the period of 1945 – 1959, the government of Indonesia held  successfully general election with 39 political parties as well as mass organization and group of constituens which all together 100 participants in the general election. From 1959 until 1966, democracy which was took on called Guided Democracy.During this period there was no general election eventhough some political parties were permitted to exist by the current rezime . The rezime was of the opinion that the Indonesian people was not ready yet for carrying out generah election. After aborted Communist coup d’etat at 30 September 1965, new government arised, and they called their government as New Order or Orba in Bahasa Indonesia. The new order remained to adopt democracy in political system which was labelled as Democracy Pancasila, referred to the nation and state philosophy. The new order government organized six  times general election which was held in 1971 1977, 1982, 1987, 1992 and 1997. In general election 1973 there was  10 political parties and 1 mass organization called Golkar, formed by government as main political power of Orba. Since 1977 the election participants were only two parties, the United Party for Development (PPP), the Indonesian Democratic Party (PDI) and Golkar. Then Golkar developed as hegemonic party, ardent and strong supporter to the Orba government, and always winning  in every general election. When Reformation Era came in 1998, the reformation government named its democracy as Demokrasi Reformasi, and as of 1998 until now, had successfully organized 4(four) times general elections with its participants fluctuated.  In 1999’s general election the participants was 48 political parties, 2004’ election was 24 parties, 2009’ s election was 38 parties, 2014’ general election was 12 parties. For 2019’ s general election, 16 parties was declared by the General Election Commission  or KPU as participants nationally.From theoretical perspectives on democracy, whatever labelled or named, democracy implemented  in Indonesia  formally as DEMOCRACY.Key words : Democracy. Political Parties, General Election.